Women Entrepreneurship: A Systematic Review to Outline the Boundaries of Scientific Literature - Cardella, Giuseppina Maria; Hernández-Sánchez, Brizeida Raquel; Sánchez-García, José Carlos (Frontiers in Psychology, 2020)
In recent years, the study of women entrepreneurship has experienced great growth, gaining a broad consensus among academics and contributing above all to understanding all those factors that explain the difficulty of women in undertaking an entrepreneurial career. This document tries to contribute to the field of study, thanks to a systematic analysis through the publications present in the topic. For this purpose, 2,848 peer-reviewed articles were analyzed, published between 1950 and 2019, using the Scopus database (SCImago Research Group). Through the use of a series of bibliometric indicators it was possible to define the current state of research on the international scene. The analysis revealed that it is a multidisciplinary field of study and that has started to expand further since 2006, culminating in 2019, which makes it become a current and valid object of study. The analysis of the clusters allowed to isolate 6 different lines of research in which emerged, on the one hand, the importance of entrepreneurial education, social entrepreneurship and the socio-cultural context of reference (e.g. culture, family and institutional support) as tools to overcome the gender gap, on the other, the importance that women entrepreneurship assumes in the economic growth of the country (especially in developing economies), promoting social inclusion and combating poverty and discrimination. The study presents an important contribution to reflect on current policies and to outline future lines of investigation.